2000
DOI: 10.1126/science.290.5490.341
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Compartmentalization in Yeast by Messenger RNA Transport and a Septin Diffusion Barrier

Abstract: Asymmetric localization of proteins plays a key role in many cellular processes, including cell polarity and cell fate determination. Using DNA microarray analysis, we identified a plasma membrane protein-encoding mRNA (IST2) that is transported to the bud tip by an actomyosin-based process. mRNA localization created a higher concentration of IST2 protein in the bud compared with that of the mother cell, and this asymmetry was maintained by a septin-mediated membrane diffusion barrier at the mother-bud neck. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
351
1
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(369 citation statements)
references
References 21 publications
10
351
1
4
Order By: Relevance
“…Therefore, it might be the defect of actin cable-based transport, which leads to the phenotype observed when AgBNI1 is deleted. It is known from several studies, that actin cables can serve as tracks for different cargos such as secretory vesicles (Johnston et al, 1991) and several organelles (Simon et al, 1995;Hill et al, 1996;Hoepfner et al, 2001;Rossanese et al, 2001) as well as mRNA (Bobola et al, 1996;Sil and Herskowitz, 1996;Takizawa et al, 2000). Using the AgSec4p fused to GFP, we were able to show that secretory vesicles use actin cables for accumulation at the hyphal tips.…”
Section: Agbni1p and The Actin Cytoskeletonmentioning
confidence: 57%
“…Therefore, it might be the defect of actin cable-based transport, which leads to the phenotype observed when AgBNI1 is deleted. It is known from several studies, that actin cables can serve as tracks for different cargos such as secretory vesicles (Johnston et al, 1991) and several organelles (Simon et al, 1995;Hill et al, 1996;Hoepfner et al, 2001;Rossanese et al, 2001) as well as mRNA (Bobola et al, 1996;Sil and Herskowitz, 1996;Takizawa et al, 2000). Using the AgSec4p fused to GFP, we were able to show that secretory vesicles use actin cables for accumulation at the hyphal tips.…”
Section: Agbni1p and The Actin Cytoskeletonmentioning
confidence: 57%
“…It has been reported that many mRNAs and RNA-binding proteins are localized to specific compartments, along with cytoskeletal elements, in a variety of eukaryotic cells (Jansen, 2001;Kloc et al, 2002). In S. cerevisiae, many mRNAs are localized to produce proteins in specific compartments such as the daughter cell or the mitochondria (Corral-Debrinski et al, 2000;Takizawa et al, 2000;Jansen, 2001;Kwon and Schnapp, 2001;Shepard et al, 2003). These observations suggest that individual mRNAs may be consistently transported to specific areas in the yeast cell.…”
Section: Discussionmentioning
confidence: 97%
“…Considering the high similarity of the expression patterns of SEPT4, SEPT7, and SEPT12, it is highly likely that the SEPT4/7/12 complex not only constitutes the structural basis of the annulus but also serves as a diffusion barrier between the various subcellular compartments of mammalian spermatozoa [6,11,35,36]. As alterations in the expression of one septin can lead to altered expression of other septins [5], the concomitant use of multiple markers (SEPT4 + SEPT7 + SEPT12) may be superior to any single marker as a sperm-quality index.…”
Section: Discussionmentioning
confidence: 99%